Bufotenine is able to block rabies virus infection in BHK-21 cells - Hugo Vigerelli; Juliana Mozer Sciani; Carlos Jared; Marta Maria Antoniazzi; Graciane Maria Medeiros Caporale; Andréa de Cássia Rodrigues da Silva; Daniel C Pimenta (Journal of Venomous Animals and Toxins including Tropical Diseases, 2014)
Background Rabies is a fatal zoonotic neglected disease that occurs in more than 150 countries, and kills more than 55.000 people every year. It is caused by an enveloped single stranded RNA virus that affects the central nervous system, through an infection initiated by the muscular nicotinic acetylcholine receptor, according to many authors. Alkaloids, such as acetylcholine, are widespread molecules in nature. They are present in numerous biological fluids, including the skin secretion of many amphibians, in which they act (together with proteins, peptides and steroids) as protection agents against predators and/or microorganisms. Among those amphibians that are rich in alkaloids, there is the genus Rhinella.Methods Bufotenine was isolated from Rhinela jimi skin secretion after a liquid-liquid partition (H2O:CH2Cl2) and reversed phase high-performance liquid chromatography analyses (RP-HPLC). Bufotenine was also extracted from seeds of Anadenanthera colubrina in acetone solution and purified by RP-HPLC, as well. Structural characterization was performed by mass spectrometry and nuclear magnetic resonance analyses. Cytotoxic tests of bufotenine were performed over baby hamster kidney (BHK-21) cells using MTT test. For the antiviral activity,Rabies virus strain Pasteur vaccine (PV) was used on fluorescence inhibition test and fluorescent foci inhibition test, with both simultaneous and time course treatment of the cells with the virus and bufotenine.Results In the present work we describe the effects of bufotenine, obtained either from toads or plants, that can inhibit the penetration of rabies virus in mammalian cells through an apparent competitive mechanism by the nicotinic acetylcholine receptor. Moreover, this inhibition was dose- and time-dependent, pointing out to a specific mechanism of action.Conclusions This work do not present or propose bufotenine as a drug for the treatment of rabies due to the hallucinogen and psychotropic effects of the molecule. However, continued studies in the elucidation of ...